Regulation of the innate immune response in rheumatoid arthritis - Muheremu, Aikeremujiang; Aierxiding, Shalayiding; Gao, Jian (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA) is a common inflammatory joint disorder characterized by progressive joint destruction, leading to painful deformity and limited mobility, for which there is currently no effective cure. While existing treatments offer symptom relief, a significant unmet need persists due to inadequate disease control in many patients. Global epidemiological studies estimate that the current incidence of RA ranges from 20 to 50 cases per 100,000 people annually, with a prevalence of 0.5% to 1.0%. The disease disproportionately affects women (2-3 times more than men) and peaks in older age groups (65-69 years). This ongoing disease burden highlights the importance of understanding its underlying mechanisms. RA is a complex autoimmune condition with a multifactorial etiology involving genetic susceptibility, environmental factors, and dysregulated immune responses characterized by autoantibody production, chronic inflammation of the synovium, and progressive joint damage. Its pathogenic process involves activating various immune cells, which significantly contribute to disease development. Extensive experimental research and clinical trials have demonstrated the different roles of the Innate Immune System (IIS) in RA. However, the scientific community remains divided on defining the composition and functions of the IIS during the onset and progression of RA. Therefore, it is essential to further investigate the role of the IIS and its relationship with the Adaptive Immune System (AIS) in RA treatment. This review covers the regulatory effects and biological functions of the Innate Immune Response (IIR), explores the underlying mechanisms of RA, and offers insights into potential biomarkers and therapeutic strategies, enhancing current understanding of the IIR for future research.